2004
DOI: 10.1080/0952398032000105076
|View full text |Cite
|
Sign up to set email alerts
|

Integration of ICT in Teacher Education and Different School Subjects in Latvia

Abstract: The introduction of information and communication technology (ICT) to the educational system of Latvia has implemented infrastructural planning since 1985 (Grinfelds, 1996). The initial plan envisaged equipping schools (mainly secondary schools) and institutions of higher education with computer sets, and training teachers and university faculty. A new subject -informatics -was introduced in secondary schools. A new syllabus was designed and, subsequently, textbooks and study aids were published. Teachers of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Many authors and teacher educators have explored the introduction and use of information and communication technologies in the school classroom from a variety of international perspectives (Baskin & Williams, 2006;Kangro & Kangro, 2004;Lim et al, 2003;Misra, 2006;Vavouraki, 2004). What is clear from this body of work is that technologies cannot be introduced in an ad hoc or top-down manner.…”
Section: Resultsmentioning
confidence: 99%
“…Many authors and teacher educators have explored the introduction and use of information and communication technologies in the school classroom from a variety of international perspectives (Baskin & Williams, 2006;Kangro & Kangro, 2004;Lim et al, 2003;Misra, 2006;Vavouraki, 2004). What is clear from this body of work is that technologies cannot be introduced in an ad hoc or top-down manner.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, our findings demonstrate that sometimes intrinsic factors, such as a teacher`s orientation towards relational goal achievement, limit the teacher`s interest in technology and its application in teaching practice. In fact, we argue that teachers with relational motivation might not fully support the integration of digital skills and competences which, according to policy goals, students in Latvia and Estonia are supposed to learn along with subject knowledge (Mägi, 2006;Kangro & Kangro, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…(PT interview form, participant 6). Kangro and Kangro (2004) remarked that it was necessary to train practitioners as a preliminary preparation for ICT integration. Further research has shown that training ICT integration practitioners within the context of professional development activities is important and in-service training has become necessary (Akbaba-Altun, 2006;Kangro & Kangro, 2004;Tondeur, Van Keer, Valcke, & van Braak, 2008).…”
Section: Findings and Discussion On The Contribution Of The Teaching mentioning
confidence: 99%
“…Kangro and Kangro (2004) remarked that it was necessary to train practitioners as a preliminary preparation for ICT integration. Further research has shown that training ICT integration practitioners within the context of professional development activities is important and in-service training has become necessary (Akbaba-Altun, 2006;Kangro & Kangro, 2004;Tondeur, Van Keer, Valcke, & van Braak, 2008). Therefore, it can be argued that for prospective teachers to experience an ICT integration transformation, they should be trained in ICT integration and application in the pre-service period, meaning that teaching practice courses need to provide opportunities for prospective teachers to develop and practice their ICT integration skills and to gain experience in relation to ICT integration.…”
Section: Findings and Discussion On The Contribution Of The Teaching mentioning
confidence: 99%